Manifestation of Sharia Regional Regulations in Managing Social Morality - Muhammad Sabir; Nazaruddin Nazaruddin (JURIS (Jurnal Ilmiah Syariah), 2021)
This study discuss about the manifestations of shariah perda in managing of sosial morality. The type of this research is a qualitative descriptive using the sociological, historical and normative juridical approaches. The results of this study suggest that the sharia regional regulations are established based on the Koran and hadith. In the history of its formation, it is inseparable from the formation of national law by observing the three periods of its formation, especially regarding regional autonomy. It is also necessary to understand that if you look at the position of regional regulations, especially sharia regulations by looking at the legal system in force in this country, it can be understood that Islamic sharia has an important position in the formation of law in Indonesia. This regulation aim of safeguarding and protecting the dignity of the community. Although there is opposition and rejection of it, this rule is in accordance with the national legal system and makes a great contribution to managing people's lives. Because one of the functions of law is to regulate or control the actions and behavior of the community so as not to do actions that are detrimental to themselves and to the surrounding community.